FAKTOR - FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG MIGRAN ETNIS MINANG MASAKAN PADANG DI KOTA DENPASAR - Enggoresta, Yosia; Wardana, I Gede (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 7, No. 5, Mei 2018 (pp. 868-1111), 2018)
ABSTRACT Migration is one of the demographic components that affect the rate of population growth. The Minangkabau tribe in West Sumatra, one of which is widely known for migration. The Minangkabau etnic known as the great monk for most people. This can be seen from the number of successful Minang people in their overseas areas. The ethnic Minang who work as Traders have large numbers in Bali Province. Padang cuisine becomes one of the famous trading assets in the culinary category for the wandering Minang ethnic. There are several factors that can affect the business income and this is the reason why many Minang people can succeed in the overseas lands. This study aims to determine whether the factors of work ethic, work experience and capital affect simultaneously and partially to the income of traders of ethnic Minang in Denpasar. The technique of analysis used is linear regression. The results showed that simultaneously and partially work ethic variables, work experience and capitalyhave a positive and significant influence on the income of traders of ethnic Minang in Denpasar. Keywords : ethnic minang, migration, trader, padang cuisine, income, work ethic, work experience, capital